Molecular biology of the gene - Watson, James D. (New York: Pearson Education, 2008)
Completely up-to-date with the latest research advances, the Sixth Edition of James D. Watson???s classic text, Molecular Biology of the Gene retains the distinctive character of earlier editions that has made it the most widely used book in molecular biology. Twenty-two concise chapters, co-authored by six highly respected biologists, provide current, authoritative coverage of an exciting, fast-changing discipline. Every chapter includes thorough content updates, and where relevant, the inclusion of medical insights that have emerged from our understanding of basic molecular biology, and references that direct students to explore the expanded companion website.
Include bibliographical references; Index 819-841p.
Keywords: Genes; Molecular biology; Translation; Zoology